Innovation Transformation as a New Stage in the Development of Small and Medium Businesses: International Practices - Vladimir V. MATVEEV; Alla A. ANNENKOVA; Tatiana A. FILICHEVA; Tatiana A. FILICHEVA (Communications of International Proceedings, 2021)
The present research is aimed at studying the effect of innovation transformation on the small and medium business sector and the possibilities of applying innovations for business development in the Russian Federation, taking into account the best international practices. The research is theoretically and methodologically based on the academic writings of national and foreign scientists on the global monitoring of business and innovation. Quantitative and qualitative methods, including statistical data analysis, were applied in the study according to international standards. To assess the area of concern and determine developmental trends of small and medium businesses in the world and, particularly, in the Russian Federation comparing with other countries, a semantic analysis of scientific papers and foreign journals was undertaken. Furthermore, basic open-source data on the activity of small and medium businesses in more than 50 countries were collected; and the effect of innovation on the general level of business development in the countries and their entering external markets were analyzed. The research has revealed the effect of innovative technologies on small and medium business sector activity, owing to the application of digital technology through deep transformations and fundamental reconsideration of business strategies, models, processes, operations, and products. It is established that in the difficult sanitary and epidemiological COVID-19 situation the stability and competitiveness can be increased by actively introducing digitalization into entrepreneurship. In this regard, modern government policy should support small and medium businesses in their determination of commercializing innovations and simplifying the production process by means of digital technologies.
Keywords: Global Monitoring; Innovation Transformation; Digital Technology; Small and Medium Business.